Global Assessment of Nasal Polyps Research: A Scientometric Analysis of Publications During 2004-13 - Gupta, B. M.; Baidwani, Kiran; Gupta, Ritu (Journal of Information and Knowledge, 2015)
The paper examines 4117 global publications in nasal polyps, as covered in Scopus database during 2004-13, experiencing an annual average growth rate of 6.92% and citation impact per paper of 3.30. The world nasal polyps research output came from 83 countries, of which the top 10 most productive countries namely USA, UK., Germany, Turkey, Japan, South Korea, China, Italy, Belgium and India accounted for 63.15% and 91.24% share of the global publication and citation output during 2004-13. USA again contributed the largest citation share to the global citations in nasal polyps, followed by UK, Belgium, Germany, Italy, Japan, China, South Korea, Turkey and India during 2004-13. The top 10 most productive countries share of international collaborative papers in nasal polyps varied from 6.25% to 53.70% during 2004-13, with highest share coming from Belgium, followed by UK, China, Germany, Italy, USA, Japan, South Korea, India and Turkey during 2004-13. Medicine contributed the largest publication share (90.72%), followed by immunology&microbiology (10.98% share), biochemistry, genetics&molecular biology (5.68% share) and pharmacology, toxicology&pharmaceutics (3.13% share) during 2004-13. The 15 most productive Indian organizations contributing to global nasal polyps research have contributed 690 publications, accounting for 16.76% to its total output during 2004-13. The average productivity per organization, average citation impact per publication, h-index and share of international collaborative publications of the top 15 most productive global organizations were 46, 8.99, 16.67 and 28.70%, respectively during 2004-13. The top 15 most productive journals contributing to global nasal polyps research have contributed 652 publications, accounting for 35.73% share to its global output during 2004-13.